Productivity and Firm Exit during the COVID-19 Crisis : Cross-Country Evidence - Muzi, Silvia; Jolevski, Filip; Ueda, Kohei; Viganola, Domenico (World Bank, Washington, DC, 2021)
This paper examines whether the economic crisis induced by the COVID-19 pandemic exhibits a Schumpeterian “cleansing” of less productive firms. Using firm-level data for 31 economies, the study finds that less productive firms have a higher probability of permanently closing during the crisis, suggesting that the process of cleansing out unproductive arrangements may be at work. The paper also uncovers a strong and negative relationship between firm exit and innovation and digital presence, especially for small firms, confirming the relevance of the ability to adapt to market conditions as a determinant of firm survival. Finally, the study finds evidence of a negative relationship between firm exit and a burdensome business environment, as well as between firm exit and age.